Ferramenta para análise da cobertura de redes móveis utilizando diferentes modelos de propagação - Vieira, Samuel Terra (2021)
As mobile technology grows, new related challenges are also emerging. Mobile networks bring the benefit of practicality and mobility to our daily lives, however, with base stations (BS) having limited range of signal, the quality of the user experience is directly and negatively influenced. With this coverage area restriction, it is interesting that companies seek strategic points for the allocation of BS, so that they can serve the largest number of customers and still offer a good quality of service and experience to them. What commonly happens is that a detailed study of the signal quality is not carried out before implementing new BS, resulting in places without signal coverage and/or even a poor quality of service. In this context, network coverage planning tools play an important role in determining the best location for the installation of a signal transmitter. In the current literature, there are few works and tools that suggest the positioning of an BS together with the analysis of the radio frequency spectrum. Thus, to help solve the problem and make it easy to estimate how good the antenna allocation will be, a tool for the analysis of signal coverage is implemented considering the mobile telephony offered in a given region, the study was carried out considering the region of Lavras/MG. In addition to performing the simulation, the proposed tool has resources to suggest a better positioning of the BS using the Simulated Annealing meta-heuristic for the purpose of optimizing the installation points. For this, propagation models available in the literature are used in order to suggest strategic points for the allocation of BS that ensure better coverage, and consequently a better quality of telephony communications. The simulations with different propagation models, the COST231-Hata model proved to be promising, suggesting new locations that promise a coverage of up to 17.4% more than the initially covered area, using different power and height values.